2018
DOI: 10.1093/jme/tjy046
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Sucking Louse (Phthiraptera: Anoplura: Polyplacidae) From the Gray Mouse Lemur, Microcebus murinus (Primates: Cheirogaleidae), in Madagascar

Abstract: Lemurpediculus madagascariensis sp. nov. (Phthiraptera: Anoplura: Polyplacidae) is described from the Gray Mouse lemur, Microcebus murinus (J. F. Miller) (Primates: Cheirogaleidae), from Ankarafantsika National Park, Madagascar. Lemurs were trapped using Sherman Live Traps and visually inspected for lice, which were preserved in 90% ethanol. Adults of both sexes and the third-instar nymph of the new species are illustrated and distinguished from the four previously known species of Lemurpediculus: L. verruculo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…Differences in host body mass, movement patterns, spatial behaviour, and minor immunocompetence of males could provide a greater variety of niches for ectoparasites infestation, as they can withstand a higher number of arthropods (Balashov et al 2007). Our study showed no record of male tick species, as mentioned by Durden et al (2018) that they naturally do not feed on host skin.…”
Section: Discussioncontrasting
confidence: 59%
“…Differences in host body mass, movement patterns, spatial behaviour, and minor immunocompetence of males could provide a greater variety of niches for ectoparasites infestation, as they can withstand a higher number of arthropods (Balashov et al 2007). Our study showed no record of male tick species, as mentioned by Durden et al (2018) that they naturally do not feed on host skin.…”
Section: Discussioncontrasting
confidence: 59%
“…Comparison of six 209-bp 18S rRNA sequences (4 from specimens ex M. murinus and 2 from specimens ex M. ravelobensis) with two published L. verruculosus sequences (GenBank: HM171410 and HM171409), showed a 100% identity, confirming the genus classification, but additional sequencing of fragments of the cytochrome c oxidase subunit 1 gene (GenBank: MG983747 and MG983748) revealed substantial differences to published L. verruculosus sequences (GenBank: HM171448 and HM171447). Collected specimens furthermore show variations in morphological characteristics within and between species, as well as to Lemurpediculus madagascariensis , a recently described new sucking louse species from M. murinus hosts of the Ankarafantsika National Park [ 46 ]. Lice collected in this study will therefore be conservatively addressed as Lemurpediculus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Specimens damaged in relevant features were excluded from morphological measurements of the respective characteristic, leading to unequal sample sizes. Species identification was based on morphological characteristics if possible (ticks: [ 39 – 43 ]; lice: [ 44 – 46 ]; mites: [ 47 – 51 ]) and was complemented by an additional genetic analysis of a subset of samples.…”
Section: Methodsmentioning
confidence: 99%
“…At two sites each, two sympatric host species were sampled ( M. murinus and M. ravelobensis at Ankarafantsika National Park and C. sibreei and C. crossleyi at Tsinjoarivo), while lice from Microcebus gerpi were collected from three different, geographically separated, populations. Trapping procedures have been described by Durden et al (2018) , Klein et al (2018) and Schüßler et al (2020) .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the known diversity of cheirogaleid lemurs, only few of their louse species have been described: two from mouse lemurs – Lemurpediculus verruculosus from Microcebus rufus and Lemurpediculus madagascariensis from M. murinus – and two from the related genus Cheirogaleus (dwarf lemurs) – Lemurpediculus claytoni from Cheirogaleus sibreei , and Lemurpediculus robbinsi from C. crossleyi ( Ward, 1951 ; Durden et al, 2010 , 2017 , 2018 ). Due to the high degree of host specificity among Anoplura, a number of undescribed louse species can thus be expected.…”
Section: Introductionmentioning
confidence: 99%